2022
DOI: 10.3390/ijms232415746
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Linked to Reepithelialization of Human Skin Wounds

Abstract: Our understanding of the regulatory processes of reepithelialization during wound healing is incomplete. In an attempt to map the genes involved in epidermal regeneration and differentiation, we measured gene expression in formalin-fixed, paraffin-embedded standardized epidermal wounds induced by the suction-blister technique with associated nonwounded skin using NanoString technology. The transcripts of 139 selected genes involved in clotting, immune response to tissue injury, signaling pathways, cell adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…It was reported that MMP1 and MMP9 were related to ECs’ tubular morphogenesis . Also, MMP1 is unambiguously associated with re-epithelialization, playing a role in initiating the migration of keratinocytes in wound healing …”
Section: Resultsmentioning
confidence: 98%
“…It was reported that MMP1 and MMP9 were related to ECs’ tubular morphogenesis . Also, MMP1 is unambiguously associated with re-epithelialization, playing a role in initiating the migration of keratinocytes in wound healing …”
Section: Resultsmentioning
confidence: 98%
“…We then investigated the expression of Mmp9 in keratinocytes of WT and Ddx58 −/− mice and found no significant difference between these two groups. Further, we detected the expression of other Mmps such as Mmp3, Mmp8, and Mmp12 whose expression have been linked to re-epithelialization (Ågren et al, 2022;Chang & Nguyen, 2021) and found that there was no significant difference in the expression of these MMPs between WT and Ddx58 −/− mice suggesting that TIMP-1 induced by RIG-I exerts its proliferation function in an MMP-independent manner. Although the recognized TIMP-1 was always known as an inhibitor of MMPs, its role in cell proliferation appears to be more diverse and complex.…”
Section: Discussionmentioning
confidence: 96%
“…As mentioned above, TIMP-1 has a higher affinity for MMP9, and studies have demonstrated that an abnormally high MMP/TIMP ratio is often present in nonhealing wounds (Li et al, 2013;Muller et al, 2008). Therefore, to investigate whether the expression of Mmps such as Mmp9, Mmp3, Mmp8, and Mmp12 whose expression have been linked to re-epithelialization (Ågren et al, 2022;Chang & Nguyen, 2021) were dysregulated in skin injury of Ddx58 −/− mice, we performed qPCR and confirmed that there was no significant difference in these Mmps expression between WT mice and Ddx58 −/− mice (Supporting Information: Figure 3b). What's more, we detected the expression of Il-10, Il-1β, Il-6, and Tnf-α which could be regulated by RIG-I in the process of wound healing and found there was no significant difference in the expression of them between WT and Ddx58 −/− mice (Supporting Information: Figure 3c).…”
Section: Rig-i Promotes Keratinocyte Proliferation By Inducing Timp-1...mentioning
confidence: 99%
“…Il‐6 is known to play a vital part in inflammation and activates both innate and the adaptive immune system 52 . In addition, it is known from literature that IL‐6 gene expression is elevated in reepithelization of human skin wounds 53 . Therefore, it was expected that IL‐6 would be elevated following the biopsy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…52 In addition, it is known from literature that IL-6 gene expression is elevated in reepithelization of human skin wounds. 53 Therefore, it was expected that IL-6 would be elevated following the biopsy procedure.…”
Section: Frequent In-depth Molecular Profiling Of Wound Healing Phasesmentioning
confidence: 99%